Mixed gender accommodation in acute care: Time to end another 'unfortunate experiment'. Issue 2 (April 2017) - Williams, Allison; Cross, Wendy; Darbyshire, Philip
Summary: The introduction of mixed gender wards that have permeated Australian hospitals in recent years may have begun as an ill-conceived experiment, but their continued existence despite expressed patients' wishes is an affront to modern health service provision. While the UK has witnessed an uproar resulting in a ban on mixed gender wards, Australian services have been slow to react to this trend. We examine the literature documenting the introduction of mixed gender wards, focusing especially on their evaluation by staff and patients. There is little if any evidence showing any benefits of mixed gender wards and research suggests that they are antithetical to basic human rights and person-centred care. It appears that the barrier to their eradication is little more than a short-term focus on financial 'feasibility'.